The Effect of Cep-Cepan (Castanopsis costata) Leaf Extract Ointment on Post-Incision Wound Healing in Wistar Rats - Yohani Theresia; Linda Chiuman; Chrismis Novalinda Ginting; Suhartomi Suhartomi (Biology, Medicine, & Natural Product Chemistry, 2026)
Wound healing remains a challenge in medical practice, as available topical medications are often expensive, less effective, or associated with side effects. This study aimed to evaluate the effect of cep-cepan (Castanopsis costata) leaf extract ointment on post-incision wound healing in Wistar rats using a post-test only control group experimental design. Cep-cepan leaf extract was obtained through maceration method using 96% ethanol, with 22% yield. This extract was then formulated into ointments with concentrations of 15%, 30%, and 45%, subsequently tested for physical stability, phytochemical content, and wound healing effectiveness. The results showed that cep-cepan leaf extract contained alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. In vivo tests on rats showed that ointments containing 30% and 45% extract significantly increased skin tensile strength and collagen density compared to the control group. The effectiveness of the 45% extract ointment was almost equivalent to gentamicin ointment as the standard group. This study indicates the potential of cep-cepan leaves as an alternative agent in wound care, providing clinical benefits at a more affordable cost and minimal side effects.